Achievement of Timing at the Highest Competitive Level: The Necessity of a `Driving conviction` - Janson, L.; Archer, T.; Norlander, T. (Athletic Insight - The Online Journal of Sport Psychology, 2005)
The study analyzed the responses of eight top athletes worldwide renown for their multiple Olympic Gold and other medal successes in several sports including: canoe, diving, swimming, ski marksmanship, ice-skating and marksmanship. The central issue posed during the in-depth interviews pertained to how Performance and Timing may be achieved in competitions. The interview material, analyzed according to the Empirical Phenomenological Psychological method, generated a total of 964 meaningful units, MUs, assembled in 33 categories. Six themes were identified from the interview material: a unifying "driving" thought, the long-term aspect of preparation, the direct mental preparation prior to start of competition, the experiences of athletes during performance, the coaching and external support they have received and experience of timing. A remarkable, unifying, feature of all these athletes was that each possessed a "driving" thought under which all other considerations were subjugated to the achievement of complete success at the highest level of competition. Another such feature was that participants not regarded "flow" as a necessity for top performance.